The use of temporary intraoral skeletal anchorage (TISAD) for orthodontic closure of gaps from first maxillary molars lost as a result of an injury - Angerman, Adam; Jarka, Jolanta (Forum Ortodontyczne / Orthodontic Forum, 2019)
The analysis of data shows that about 25% of schoolchildren experience tooth injuries. Sport is a very common cause of such injuries. Although only 4% of these injuries are serious, they are associated with significant consequences. Loss of a tooth/teeth always and especially at the developmental age may lead to loss of the alveolar process bone and movements of adjacent teeth. Aim. The aim of the paper was to present management including orthodontic closure of gaps after loss of two first premolars in the maxilla using skeletal anchorage in a 14.5-year-old female patient. Case report. A 14.5-year-old female patient who had suffered an injury to the facial skeleton as a result of getting kicked by a horse presented for treatment. Based on documentation and medical interview this event resulted in the extraction of two most damaged teeth – both first permanent premolars in the maxilla. In the case of this patient, treatment included the closure of gaps from lost teeth via mesialisation of second premolars and first and second molars using skeletal anchorage. Material included medical documentation: patient’s orthodontic records, diagnostic models, photographs and radiological records. Results. Satisfactory aesthetic and functional outcomes were obtained despite the fact that the patient’s had had normal occlusion before treatment. Conclusions. Orthodontic closure of gaps from permanent teeth lost as a result of a trauma may be recommended in adolescent patients as one of alternative methods of treatment. The use of temporary intraoral skeletal anchorage (TISAD) allows movements of groups of teeth and avoiding unfavourable changes of positions of teeth that are in normal occlusion.